2015
DOI: 10.1002/2015gc005800
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic water contents determined through clinopyroxene: Examples from the Western Canary Islands, Spain

Abstract: Water is a key parameter in magma genesis, magma evolution, and resulting eruption styles, because it controls the density, the viscosity, as well as the melting and crystallization behavior of a melt. The parental water content of a magma is usually measured through melt inclusions in minerals such as olivine, a method which may be hampered, however, by the lack of melt inclusions suitable for analysis, or postentrapment changes in their water content. An alternative way to reconstruct the water content of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 112 publications
(246 reference statements)
7
53
0
1
Order By: Relevance
“…Water contents corresponding to the spectra differed for the calibrations of Bell et al (1995) and Libowitzky and Rossman (1997). With the mineral-specific calibration by Bell et al (1995), values were about 15% higher, but similar to previous studies we prefer to use water contents derived through the wavenumber-dependent calibration 1 3 (e.g., Stalder 2004;Stalder and Ludwig 2007;Sundvall and Stalder 2011;Mosenfelder and Rossman 2013;Weis et al 2015Weis et al , 2016. No OH-bands were observed in the two annealed reference crystals implying water contents below the detection limit or their complete dehydration.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Water contents corresponding to the spectra differed for the calibrations of Bell et al (1995) and Libowitzky and Rossman (1997). With the mineral-specific calibration by Bell et al (1995), values were about 15% higher, but similar to previous studies we prefer to use water contents derived through the wavenumber-dependent calibration 1 3 (e.g., Stalder 2004;Stalder and Ludwig 2007;Sundvall and Stalder 2011;Mosenfelder and Rossman 2013;Weis et al 2015Weis et al , 2016. No OH-bands were observed in the two annealed reference crystals implying water contents below the detection limit or their complete dehydration.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…From this viewpoint, the presence of this hydrogen can be expressed as a water concentration. The amount of water in NAMs was shown to serve as a proxy to estimate magmatic water contents (e.g., Weis et al 2015). Similarly the hydrous component in NAMs provides information about the deep water cycle and the storage of water in the mantle of planetary bodies (e.g., Bolfan-Casanova 2005;Peslier 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen diffusion in clinopyroxene phenocrysts may also provide novel tools for volcanologists to quantify initial magmatic water contents (Wade et al 2008;Weis et al 2015;Lloyd et al in revision) and the rate of magma ascent, a key parameter determining the explosiveness of an eruption (Pyle 2000;Rutherford 2008). Hydrogen diffusion profiles in xenolithic olivine have been used to estimate ascent rates (Demouchy et al 2006;Denis et al 2013;Peslier et al 2008), and similar profiles have been observed in clinopyroxene phenocrysts (Wade et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…More studies on different types of inclusions have to be done in future to get usable numbers. A statement about the concentration is hypothetical as the precise densities (mass and atomic) of the inclusions here is unknown, but as a rough guess from the above numbers we get values of 1.0 and 0.6 wt% H 2 O assuming that the glass density and composition of the melt inclusions are similar to the density (2.72 g/cm 3 ) and whole rock composition of the ankaramite magma (see Weis et al 2015). The hydrogen signal of the remaining area corresponds to about 500 wt.…”
Section: Discussionmentioning
confidence: 90%
“…The role of this water component in geology is important since it has a big influence on mantle rheology, magma genesis and evolution as well as the character of volcanic eruptions. By measuring the water content in NAMs from volcanic rocks or mantle xenoliths, geologists can gain information on magmatic water contents as well as the storage capacity of water in the mantle of planetary bodies (e.g., Bolfan-Casanova 2005;Peslier 2010;Sundvall and Stalder 2011;Weis et al 2015Weis et al , 2017. For the analysis of OH in NAMs, various methods can be applied such as Fourier transformed infrared (FTIR) spectroscopy (e.g., Skogby 2006), secondary ion mass spectrometry (SIMS) (e.g., Wade et al 2008), elastic recoil detection analysis (ERDA) (e.g., Withers et al 2012) or Raman spectroscopy (e.g., Thomas et al 2008;Bolfan-Casanova et al 2014).…”
Section: Introductionmentioning
confidence: 99%